A new approach in evaluating the surface beta contamination using the direct method of measurement. (November 2017) - Stanga, D.; De Felice, P.; Capogni, M.
Abstract: This paper describes a new approach in evaluating the surface beta contamination using the direct method of measurement. It makes use of previous results obtained in numerical modeling of electron transport in planar geometry and is mainly based on the estimation of the efficiency of contamination sources for beta radiation and its standard uncertainty using the available information concerning the component materials of the sources and their main parameters. Experimental results illustrate the appropriateness of the new approach for surface beta contamination measurements. Highlights: A new approach in evaluating surface beta contamination is described. The approach is based on the evaluation of the source efficiency for beta radiation. It alleviates difficulties in uncertainty evaluation in beta contamination measurements.